Pengolahan Usaha Perikanan pada Produksi Benih Ikan Nila di Nagori Purwosari - Rini Mandasari; Muhammad Farhan Fadillah; Yulia Lestari; Suci Indah Sari; Cut Latifah Zahari (Universitas Pahlawan Tuanku Tambusai, 2023)
Community service activities were carried out for 4 months in Nagori Purwosari, Pematang Bandar District, Simalungun Regency, which is about 124 km from the Nusantara Al Washliyah Muslim University Medan. The partner is a tilapia farming business owned by Mr. Anwar Ma'sum Saragih Farm. Tilapia (Oreochromis niloticus) is a freshwater fish that can be farmed. The purpose of this devotion is to recognize directly about the methods of tilapia farming. Tilapia farming activities are seed stocking, feeding, water quality management, oxygen content, harvesting and marketing. Stocked seeds measuring 1−2 cm by 100,000 heads. The dose of feed is 3% by weight of tilapia. The pond is filled with irrigation water and pam water. The salinity of the water is 20 ppt, the water quality includes water PH 6.5−8.6, water temperature 25°−30°C, dissolved oxygen 5 mg/L (ppm), ammonia content (NH3) 0.02 ppm, calm water discharge 8−15 L/s/ha, water quality is not cloudy and not polluted with harmful chemicals.